Seminormed factor spaces and the theory of splines - Morozov, V.A. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2003)
Tikhonov’s theory of normal solutions is related to the method of factor spaces widely used in modern mathematics of computations. The theory of splines is developed for Hilbertian spaces as well as for some classes of normed spaces. The work was supported by the Russian Foundation for Basic Research (01-01-0398).